STUDI PERBANDINGAN PENGGUNAAN HAK CIPTA FILM SEBAGAI OBJEK JAMINAN FIDUSIA DI INDONESIA DAN AMERIKA SERIKAT - Halim, Dianita; Gunardi, Gunardi (UNES Law Review, 2023)
Film copyright as object of fiduciary guarantees has been widely used in the United States. However, in Indonesia this still has many obstacles and it is suspected that only one Indonesian film production house has ever used its film copyright as a collateral object. This research was conducted to find out the mechanism and valuation system of using film as an object of fiduciary guarantees. This type of research is empirical legal research or sociological legal research with a comparative approach. This method was used because researchers wanted to find options for valuation systems and mechanisms for using film copyright as objects of fiduciary guarantees based on legal regulations and practices that occurred in the Indonesian and United States film industries. There are similarities between the process of using film copyright as collateral objects in Indonesia and the United States. In terms of the valuation system, there are many differences between Indonesia and United States because Indonesia does not have regulations about valuation system of copyrighted assets. The United States adopted the valuation process and method from WIPO (World Intellectual Property Organization) to conduct a valuation of a Copyright. The process includes the foundation, profile, methodology (cost method, market method, or income method) stages, and ends with the solution.